Edukasi Persiapan Menghadapi Menopause di SDN 9 Merarai - Atri Rudtitasari; Arum Seftiani Lestari; Dian Ika Pratiwi (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2026)
Menopause is a natural phase marked by the cessation of menstruation for 12 months due to estrogen deficiency, which is often accompanied by challenging physical and emotional symptoms. With the increasing population of women aged over 50 years (reaching 26% in 2021), challenges related to access to information and awareness of menopausal changes have become crucial to ensure that quality of life is maintained. Objective: This community service activity aimed to improve knowledge and prepare mothers from an early stage to face menopausal changes and manage the associated discomfort. Methods: The activity was conducted at SDN 9 SP I Pandan and involved nine participants. The educational intervention was carried out in three stages: introduction and pre-test, delivery of material using PowerPoint and leaflets, and an interactive discussion session. The materials covered the definition of menopause, its stages, common symptoms, health risks, and preparation strategies through healthy lifestyles and medical check-ups. Results: The counseling session was conducted smoothly in the hall of SDN 9 SP I Pandan. Participants showed high enthusiasm, with five out of nine actively asking in-depth questions related to preparing for the menopausal transition. Through this educational activity, participants gained a comprehensive understanding of symptom management, including hot flashes, sleep disturbances, and mental health. Conclusion: This community service activity successfully provided new insights for mothers regarding the importance of preparing for menopause. The positive response from participants indicates the need for similar educational activities to be carried out regularly to build a sustainable support system for women during perimenopause and menopause.